Risk Factors for Mortality in Low Birth Weight Infants with Respiratory Distress Syndrome - Arailym Abilbayeva; Anel Tarabayeva; Nishangul Bozhbanbayeva; Dinara Yelyubayeva (Ķazaķstannyṇ Klinikalyķ Medicinasy)
Objective: To study the structure of concomitant pathologies in low birth weight premature newborns with respiratory distress syndrome (RDS). To identify mortality risk factors in these newborns. Materials and methods: Data from 374 premature newborns weighing less than 1500 g and gestational age less than 32 weeks with RDS treated in the intensive care unit were analyzed. Results: Several comorbidities were more common among children with RDS compared to children without RDS. Thus, disseminated intravascular coagulation syndrome (DIC) occurred 2 times, atelectasis 1.3 times, necrotizing enterocolitis (NEC) 2.4 times, and anemia 1.8 times more often among children with RDS compared to those without RDS. In multivariate logistic regression, such factors as 1-3 points on the Apgar scale at 1 minute (OR - 2.478, 95% CI - 1.289-4.764, p = 0.007), 1-3 points on the Apgar scale at 5 minutes ( OR - 3.754, 95% CI - 1.788-7.878, p<0.0001), DIC (OR -4.428, 95% CI -2.206-8.887, p<0.0001), NEC (OR - 4.508, 95% CI - 2.270-8.954, p<0.0001) showed a positive association with death in children with RDS. When assessing the effect of the combination of DIC and NEC on death, it was found that the combination of these two pathologies in children with RDS increases the risk of death by more than 2 times. Thus, the area under the curve (AUC) for DIC was 0.283, for NEC the AUC was 0.335, and for the combination ICE+NEC it was 0.782). Conclusions: The structure of comorbidities in low birth weight infants with RDS differs from that of infants without RDS. Premature infants with RDS were more likely to develop anemia, DIC, atelectasis, and NEC. The presence of comorbidities increases the risk of death in low birth weight infants with RDS. Low Apgar score, DIC syndrome, and NEC can increase the risk of death in low birth weight premature infants with RDS. It is anticipated that the collected data will enhance personalized care for low birth weight, premature infants with multiple health conditions, ultimately reducing mortality rates in this vulnerable patient group.